Faktor Risiko Kanker Payudara - Syifa Hero (Yayasan Pendidikan Medika Indonesia, 2021)
Cancer is a non-communicable disease characterized by the presence of abnormal cells that can grow uncontrollably and have the ability to attack and move between cells and body tissues. Breast cancer is the most common cancer in women and the second leading cause of related death after lung cancer. This disease is a health problem that tends to increase every year. Breast risk factors are known to avoid cases of this disease. The purpose of this paper is to determine the risk factors for breast cancer. The method used is literature research by searching for the words cancer, breast, malignancy, breast cancer, and mammary in Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion and comparison of the results presented in the article. From several studies conducted, the risk factors for breast cancer are a family history of breast cancer, gestational age of the first child, age at birth of the first child, nulliparous parity, history of breastfeeding, obesity, and physical activity.